Eficiência de um sistema silvipastoril em substituição à adubação nitrogenada e a sua relação com a dinâmica da matéria orgânica em solo distrocoeso - Ramos, Laís Silva (2013)
The ecoregion of Coastal Tablelands has characteristics of soil and climate that hinder the production agricultural, livestock and forestry. Given this, alternative practices in rural production, like the silvopastoral systems, emerge in conducting economic benefits and improvement of soil fertility. Silvopastoral systems in the use of leguminous trees in interaction with the grassy can likely to substitute the need for nitrogenous fertilizer, besides promote an increase in biomass content deposited in the soil benefiting organic matter dynamics. The aim of this study is to evaluate the influence the cultivation of Brachiaria Brizantha in different levels of nitrogen fertilizer in the form of urea (0, 80, 160, 240 kg N ha-1) and in interaction with Gliricidia sepium in quantity and quality of organic matter in a dystrophic cohesive yellow latosol in the Coastal Tablelands. Soil samples were collected in July of the year 2012 at the experimental field the Jorge do Prado Sobral, pertecente the Research Center Coastal Plains of Brazilian Company of Agriculture Research (EMBRAPA), in the city of Nossa Senhora das Dores, state of Sergipe, which were sent to conduct physical and chemical analyzes in the laboratory. This scientific work determined the density of the soil, physical and chemical fractionation of organic matter, total organic carbon and total nitrogen, carbon and nitrogen stocks of soil, basal respiration rate and carbon management index. According to the results, in the superficial layer, the Brachiaria Brizantha crops fertilized with a dose of 240 kg N ha-1 and silvopastoral system provided an increase in carbon stocks, the application of nitrogenous fertilizer in dose of 240 kg N ha-1 was effective in carbon accumulation and maintenance in different humic fractions; the silvopastoral system due to the lower rate of respiration can be considered a management more sustainable for the region; in the different soil layers, the contents of MOP and MOAM were more sensitive to changes in soil land use when compared to the basal respiration. The introduction of silvopastoral system demonstrated results, for the most part, favorable for the different variables analized, especially in the superficial layer, thus constituting a viable option in the substitution of nitrogenous fertilizer and maintenance of soil fertility.